Architecture and Features of Mobile Communication Satellite System for Mobile Phone - Dong CHEN; Qian ZHANG; Zhaotao QIN; Jincheng TONG (天地一体化信息网络)
The development and construction of mobile communication satellite systems for individual users worldwide have been ongoing for over thirty years, and the technological level and industrial scale of satellite mobile communication are constantly maturing.Under the trend of deep integration of satellite communication and ground communication systems, the new generation of mobile communication satellites that support mobile phone connection is a new direction for the development of satellite-ground convergence.This paper expounded the development prospect and driving force of satellite system supporting mobile phone connection, proposed the mobile communication satellite network architecture based on GSO satellite and LEO satellite constellation, and analyzed the network characteristics and satellite technical challenges introduced in the above architecture from the perspective of satellite.Finally, the network communication system and related key issues were discussed.